Foreign Body Induced Neuralgia: A Diagnostic Challenge - S. Padmashree; Chaitra H. Ramprakash; Rema Jayalekshmy (Case Reports in Dentistry)
Neuropathic pain is caused by neural injury or painful states associated with either peripheral or central nerve injury. One of the aetiologies of this type of pain is iatrogenic trauma. This case highlights the features of peripheral neuropathic pain caused by foreign body left in the mental foramen following a previous surgical procedure. The foreign body was detected on routine radiographic evaluation. Once the foreign body was removed by surgical intervention, the pain resolved. This stresses the importance of routine radiographic evaluation in proper diagnosis and treatment planning in the management of neuropathic pain. This paper also sheds light on the role of iatrogenic mechanical cause of peripheral neuropathic pain and warrants a tough degree of caution on the part of oral clinicians.